UJICOBA SUPLEMENTASI BESI ASAM FOLAT DAN VITAMIN B12 UNTUK MENANGGULANGI ANEMIA - Vita Kartika; Sri Prihatini; Syafrudin Syafrudin; Iman Sumarno (Persagi, 1998)
An experiment was done to cope with anemia in subdistrict Cugenang, District Cianjur, West Java. By supplementation iron pills, folic acid and vitamin B12, the experiment was carried out among women of productive age. The three supplements were given to 135 women once a week over a duration of four months. The women were divided into four groups. Group I (control) was given placebo, group II was given iron pills. Folic acid and vitamin B12 (as the programme of heath centre), while group IV was given iron pills and vitamin B12. Observation on haemoglobin (Hb) from blood samples was done once a month during the four months. The results showed that the 135 women had relatively equal initial Hb contents. Group I had 9,32 gr/l, group II had 9,08 gr/l, group III had 9,09 gr/l and group IV had 9,00 gr/l. At the end of the fourth month, the Hb contents increased, except that of group I. Group II showed an increased to 11,92 gr/l, group III to 12.09 gr/l and group IV to 11.87 gr/l. A statistical examination explained that group II -IV were significantly different from group I, but there was not any significant difference among the three groups. It was obvious that the highest increase in Hb content belongs to group III, being 3,00 gr/l, leading to the largest decrease in the percentage of anemic condition, being 69,6%. The smallest decrease 61,2%, belong to group II, while 67,8% was the decrease of group IV. Group I did not show any decrease in the percentage of anemic condition. The increase in Hb contents was evidence that three supplement could improve the condition of the women. Iron pills, folic acid and vitamin B12 combined together proved to be the best intervention. However, in case of insufficiency or impossibility, iron pills and folic acid (as the programme of heath centre) were considered to be good supplements to improve the Hb contents.Keywords: anemia, nutritional supplements, haemoglobin (HB)